Epidural versus intravenous fentanyl for postoperative analgesia following orthopedic surgery: randomized controlled trial - Privado, Marcelo Soares; Issy, Adriana Machado; Lanchote, Vera Lucia; Garcia, João Batista Santos; Sakata, Rioko Kimiko (São Paulo Medical Journal, 2010)
CONTEXT AND OBJECTIVE: Controversy exists regarding the site of action of fentanyl after epidural injection. The objective of this investigation was to compare the efficacy of epidural and intravenous fentanyl for orthopedic surgery. DESIGN AND SETTING: A randomized double-blind study was performed in Hospital São Paulo. METHODS: During the postoperative period, in the presence of pain, 29 patients were divided into two groups: group 1 (n = 14) received 100 µg of fentanyl epidurally and 2 ml of saline intravenously; group 2 (n = 15) received 5 ml of saline epidurally and 100 µg of fentanyl intravenously. The analgesic supplementation consisted of 40 mg of tenoxicam intravenously and, if necessary, 5 ml of 0.25% bupivacaine epidurally. Pain intensity was evaluated on a numerical scale and plasma concentrations of fentanyl were measured simultaneously. RESULTS: The percentage of patients who required supplementary analgesia with tenoxicam was lower in group 1 (71.4%) than in group 2 (100%): 95% confidence interval (CI) = 0.001-0.4360 (P = 0.001, Fisher’s exact test; relative risk, RR = 0.07). Epidural bupivacaine supplementation was also lower in group 1 (14.3%) than in group 2 (53.3%): 95% CI = 0.06-1.05 (P = 0.03, Fisher’s exact test; RR = 0.26). There was no difference in pain intensity on the numerical scale. Mean fentanyl plasma concentrations were similar in the two groups. CONCLUSION: Intravenous and epidural fentanyl appear to have similar efficacy for reducing pain according to the numerical scale, but supplementary analgesia was needed less frequently when epidural fentanyl was used. CLINICAL TRIAL REGISTRATION NUMBER: NCT00635986